Hubungan Motivasi Belajar dengan Hasil Belajar Bahasa Indonesia Siswa Kelas XI - Santhy Dewi Putri P; Sri Rahayu (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
This research is motivated by the importance of learning motivation on learning outcomes at school. A person will not get good learning outcomes without motivation. This motivation can come from within and from outside. Therefore, it is necessary to conduct research on the relationship between learning motivation and learning outcomes in Indonesian. This type of research includes descriptive research using quantitative approaches and correlation methods. The population and sample of the study were all students of class XI SMA Negeri 1 Siak Hulu, totaling 4 classes, namely XI IPA1 as many as 20 students, XI IPA2 as many as 20 students, XI IPS1 as many as 24 students and XI IPS2 as many as 25. The sampling technique in this study used a technique Nonprobability is a saturated sample. Data collection techniques are observation, questionnaires and interviews. The results of the study concluded that there was a significant influence on learning motivation in Class XI at SMA Negeri 1 Siak Hulu, this was evidenced by t count (3,462) > from t table (1,979) with a significant level of 0.05 then Ho was rejected and Ha was accepted. Then the hypothesis is accepted. This shows that there is an influence of motivation on learning outcomes